The role of innovativeness in the relationships between ethical sensitivity, knowledge sharing intensity, access to ICT and access to finance and sustainable performance of SME's - Adamu, Amina Asabe (2021)
Small and Medium Enterprises (SMEs) play a dynamic role in the sustainable development of any nation. They are the core of an economic system as they provide employment and contribute to Gross Domestic Product (GDP) of a country. The sustainable performance SMEs as a strategy of national sustainable development is therefore of utmost importance. This study examines the sustainable performance of SMEs based on Triple Bottom Line (TBL) approach and the factors affecting SMEs sustainable performance as derived from Resource Base View (RBV) theory and the Dynamic Capabilities theory. More specifically, this study investigates the relationships between ethical sensitivity, knowledge sharing intensity, access to ICT, access to finance, sustainable performance in Nigeria. The moderating role of innovativeness on these relationships to sustainable performance was also examined. Data was analysed using Partial Least Squares Structural Equation Modelling (PLSSEM). The study found that there are significant positive relationships between ethical sensitivity, knowledge sharing intensity, access to finance and sustainable performance of SMEs. In addition, it was also found that innovativeness positively moderates the relationship between access to ICT and sustainable performance as well as the relationship between access to finance and sustainable performance of SMEs. However, access to ICT has no significant effect on the sustainable performance of SMEs. The research recommends that SMEs should focus on securing access to finance, increasing knowledge sharing intensity, ethical sensitivity and access to ICT as well as developing innovativeness to achieve sustainable performance. This research contributes to SME literature by integrating the theories on Triple Bottom Line (TBL), Resource Base View (RBV) and Dynamic Capabilities to sustain their performance. This study benefits various stakeholders by highlighting the effects of ethical sensitivity, knowledge sharing intensity, access to ICT, access to finance and innovativeness on the sustainable performance of SMEs.